The format of training family doctors on palliative care in the Dnipropetrovsk region. - I. L. Vysochina (Medičnì Perspektivi, 2020)
The first global palliative care resolution WHA 67.19 has been developed recently, in 2014, where the need to improve access to palliative care around the world is first declared. In the article, the authors analyzed the change trends and the state of the medical care delivery system for incurable patients in the world and Ukraine. As the civilization of the state and the humanity of society as a whole is assessed by the level of PHC provision in today's world, this problem has attracted the attention of central (Ukraine) and regional (Dnipro city) government bodies, which was reflected in the search for new medical and educational initiatives. The need of the time is the need to focus the attention of family doctors on the issue that palliative care is a qualification component of their daily work, which will help to remove incurable patients from the periphery of attention of their multicomponent work, and will also help to clearly build the interaction between the primary and secondary link, in particular, with hospice departments of specialized hospitals. In particular, the experience of implementing a joint project of a new format for training family doctors on palliative care issues, realized by the Department of Family Medicine of the SE “DMA” and the Municipal non-commercial enterprise "City Clinical Hospital No. 2” of Dnipro City Council is described. Innovative forms of conducting classes help to expand the boundaries of the possibilities of teaching problematic issues of palliative medicine, which account for only 0.6% of instructional time in the existing program of training family doctors of secondary specialization, and the multicomponent format for studying palliative care issues, implemented, inter alia, with support of Director of the Municipal non-commercial enterprise "City Clinical Hospital No. 2” of Dnipro City Council (visiting hospice and palliative departments delivering secondary level of medical care assistance, a structured regulatory unit for the provision of PHC in Ukraine, working out of patients’ routing issues, interactive teaching methods, etc.) leaves in the memory of physician-trainees not only the essential content, but also a deep emotional trace, which helps to increase the motivation of the physician trainees, improves coordination between primary and secondary palliative care and improves the quality of training.